Acute Disseminated Encephalomyelitis Following Typhoid Fever: A Case Report - Adhikari, R; Tayal, A; Chhetri, PK; Pokhrel, B (Journal of College of Medical Sciences-Nepal, 2014)
The involvement of central nervous system in children with typhoid fever is common. Acute disseminated encephalomyelitis is a rare immune mediated and demyelinating disease of the central nervous system that usually affects children. We report a 7-year-old child with typhoid fever who developed acute cerebellar syndrome due to acute disseminated encephalomyelitis. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-4, 55-58 DOI: http://dx.doi.org/10.3126/jcmsn.v9i4.10237